Consumption of distinct dietary lipids during early pregnancy differentially modulates the expression of microRNAs in mothers and offspring. - Patricia Casas-Agustench; Flavia S Fernandes; Maria G Tavares do Carmo; Francesco Visioli; Emilio Herrera; Alberto Dávalos (PLoS ONE, 2015)
Diet during pregnancy and lactation influences the offspring's health in the long-term. Indeed, human epidemiological studies and animal experiments suggest that different type of fatty acids consumption during pregnancy affect offspring development and susceptibility to metabolic disorders. Epigenetic changes are thought to be elicited by dietary factors during critical timing of development. microRNAs (miRNAs) are versatile regulators of gene expression. Thus, we aimed to determine the influence of different fatty acids on miRNA expression in offspring when given during early pregnancy. We fed pregnant either soybean (SO), olive (OO), fish (FO), linseed (LO), or palm-oil (PO) diets from conception to day 12 of gestation; and standard diet thereafter. miRNA expression was assessed in liver an adipose tissue of pregnant rats and their virgin counterparts. While liver concentrations of fatty acids in pregnant or virgin rats replicated those of the diets consumed during early pregnancy, their pups' liver tissue marginally reflected those of the respective experimental feeds. By contrast, the liver fatty acid profile of adult offsprings was similar, regardless of the diet fed during gestation. Different parental miRNAs were modulated by the different type of fatty acid: in adult offspring, miR-215, miR-10b, miR-26, miR-377-3p, miR-21, and miR-192 among others, were differentially modulated by the different fatty acids fed during early pregnancy. Overall, our results show that maternal consumption of different types of fatty acids during early pregnancy influences miRNA expression in both maternal and offspring tissues, which may epigenetically explain the long-term phenotypic changes of the offspring.